Microaspersion of phosphites during cold storage of Fuji apples fruit cv. aiming to control postharvest decay - Brackmann, Auri (2007)
The objective of this work was to evaluate the effect of microaspersion of potassium phosphite, during cold storage, on the control of postharvest decay in cv. Fuji apple fruit. The evaluated treatments were: [1] water (control); [2] potassium phosphite A 00 – 40- 20; [3] potassium phosphite B 00-40-20; [4] potassium phosphite B 00-30-20; [5] potassium phosphite B 00-28-26. Fruits were stored at - 0.5°C and 94 ± 2% of air relative humidity. Microaspersions were performed in the cold chamber free space at the beginning of storage and each 30 days during two months. Microaspersion of phosphites did not control postharvest decay after two and three months of cold storage of cv. Fuji apple fruit.